شعرية التأليف في كتاب "المقتطف من أزاهر الطرف" لابن سعيد الأندلسي (الشعرية ، التأليف، الانزياح ، أزاهر الطرف) - ساجت هداب, سناء (Al-Adab Journal, 2018)
The researcher presents an additional evidence about the critical ability and the exclusivenss in authorship distinguishing the poet, writer, critic, and voyager Ali Bin Musa Bin Sa'yd Al-Andulusi (died 685 Higri).This is done by studying his book"Al- Muqtataf Min Azahir Al – Taraf IbnSa'yd Al- Andulusiin which he had a special authorship .It was different from all his writings where it wasn't in accordance with the usual in the literary selections achieving poetic writing in the type of choic,describing his book as containing poetic and prose texts according to objective and artistic special limitations which he arranged on the basis of a system that achieves the reference of the title of the book. He divided the book into chapters, calling each one(Khamila) and he supported the poetic authorship with the distribution method which is based on a strict system concerning the number of chapters and texts implied in them, not mentioning the terminologyies which he uniquely used to label poetic and prose samples.Moreover he subjected these chosen samples to revising issues. He also summarized these textes to be suitable for the criteria which he used to sort out the prototype which wasn't labeled before.